A Critical Discourse Analysis of Former Davao City Mayor Sara Duterte’s State of the City Addresses (SOCAs) - Aperocho, Maico Demi B.; Flores, Seth A.; Gabisan, Jenyvive G.; Ygay, Noevy Jane B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study examined the discourses in the State of the City Addresses (SOCAs) of the former Mayor Davao City Sara Duterte-Carpio. Specifically, the rhetorical expressions, semantic expressions, linguistic features, and classifications of ideologies in the political discourses were explored. Through a Critical Discourse Analysis, the researchers explored the use of language and the ideologies represented in such. Findings show that the SOCAs of former Davao City Mayor Sara Duterte-Carpio contained a variety of rhetorical expressions and discourse patterns. The researchers also found significant results about semantic macrostructures, which vary from one speech to another. The ideology of positive Us was also represented through powerful statements that show the importance of former Mayor Sara's leadership, administration, projects, and all people involved in her success. The researchers conclude that the former Davao City Mayor used words powerfully to highlight essential accomplishments and to express the value of the critical actors that made these achievements possible.